The effects of flavoxate hydrochloride on voltage-dependent L-type Ca(2+) currents in human urinary bladder - Tomoda, Toshihisa (2005)
1. The effects of flavoxate hydrochloride (Bladderon®, piperidinoethyl-3-methylflavone-8-carboxylate; hereafter referred as flavoxate) on voltage-dependent nifedipine-sensitive inward Ba(2+) currents in human detrusor myocytes were investigated using a conventional whole-cell patch-clamp. Tension measurement was also performed to study the effects of flavoxate on K(+)-induced contraction in human urinary bladder. 2. Flavoxate caused a concentration-dependent reduction of the K(+)-induced contraction of human urinary bladder. 3. In human detrusor myocytes, flavoxate inhibited the peak amplitude of voltage-dependent nifedipine-sensitive inward Ba(2+) currents in a voltage- and concentration-dependent manner (K(i)=10 μM), and shifted the steady-state inactivation curve of Ba(2+) currents to the left at a holding potential of −90 mV. 4. Immunohistochemical studies indicated the presence of the α(1C) subunit protein, which is a constituent of human L-type Ca(2+) channels (Ca(V)1.2), in the bundles of human detrusor smooth muscle. 5. These results suggest that flavoxate caused muscle relaxation through the inhibition of L-type Ca(2+) channels in human detrusor.